The Effect of Cooking Methods on Nutrient Retention in Foods (International Journal of Food and Nutritional Sciences, 2022)
: This research paper investigates the impact of various cooking methods on nutrient retention in foods. The primary objective is to assess how different culinary techniques affect the nutritional content of commonly consumed food items. A comprehensive literature review is conducted to contextualize the study within the existing body of research on cooking and nutrition. The study employs a systematic methodology, examining the nutrient profiles of diverse foods subjected to boiling, steaming, grilling, roasting, microwaving, and frying. Nutrient levels are analyzed using established scientific methods, and the results are presented in detail, showcasing the changes in vitamins, minerals, and other essential components across different cooking methods. The findings reveal significant variations in nutrient retention, emphasizing the importance of cooking techniques in preserving the nutritional value of foods. The discussion interprets these results in the context of existing knowledge, addressing practical implications for individuals and public health. In conclusion, the study contributes valuable insights into optimizing cooking methods for nutrient preservation, offering recommendations for healthier culinary practices and setting a foundation for future research in this critical field.